1995
DOI: 10.3109/02656739509052332
|View full text |Cite
|
Sign up to set email alerts
|

Water bath hyperthermia is a simple therapy for psoriasis and also stimulates skin tanning in response to sunlight

Abstract: An eight week trial, involving superficial hyperthermia delivered biweekly via simple water bath immersion, was tested for its ability to clear mild to moderate psoriatic lesions. Seven patients were treated and three cases rapidly improved. In the remaining patients, the treatment frequency was increased to alternate days; two cases improved significantly, one patient showed a partial response, and the fourth had no visible change (this was the only patient taking concurrent drug therapy--etretinate). In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Hyperthermia is not a new concept but research interest into its application in the treatment of psoriasis is relatively recent [28]. Early utilization of hyperthermia for psoriasis followed on from the ideas that the severity of psoriasis would reduce during warm summer months, and a benefit of hyperthermia had been shown for killing cancer cells [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperthermia is not a new concept but research interest into its application in the treatment of psoriasis is relatively recent [28]. Early utilization of hyperthermia for psoriasis followed on from the ideas that the severity of psoriasis would reduce during warm summer months, and a benefit of hyperthermia had been shown for killing cancer cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which diseases respond to balneotherapy probably incorporate chemical, thermal and mechanical effects [35]. It was suggested by a clinical study that simple repetitive water bath hyperthermia was effective in the treatment of psoriasis by improving psoriatic lesions, reducing edema and relieving pruritus [28]. In addition, the water itself could remove psoriatic scale [36], which may be beneficial for skin absorption of phototherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly used methods for generating local hyperthermia include the use of radiofrequency, 20 microwaves, 21 laser, 22 or superficial hot water applicators. 23 Temperature-sensitive DDS can be used as an adjuvant to thermal ablation to reduce the potential for tumor regrowth in regions of sublethal thermal damage such as at the ablation margin. 24 In addition, mild hyperthermia can be used to trigger drug release 25 within heated tissue and may be used just before subablative or ablative temperature elevation, potentially resulting in a “drug depot” effect whereby drug is concentrated in target tissues following local vascular shutdown.…”
Section: Advanced Drug Delivery Systemsmentioning
confidence: 99%
“…Clinical trials of adjuvant hyperthermia have demonstrated statistically significant improvement in complete response rates for small tumors but have failed to make a major impact on the disease due to limitations in the size and location of tumors that can be heated effectively with current equipment. Similar difficulties with uniform heating of large contoured areas of the body have restricted use of moderate temperature hyperthermia therapy for other clinical conditions such psoriasis, which also has been shown responsive to heat [4][5][6] .…”
Section: Introductionmentioning
confidence: 98%